(untitled) (Indian Journal of Veterinary Pathology, 2024)
Canine mammary tumors (CMT) are the most common neoplasms with worldwide distribution. It has been suggested as a model to study human breast cancer. Incidence of mammary gland tumour in canine is as high as 50 per cent of all neoplasms when compared with breast cancer in human beings (27%). The present study was performed to assess the occurrence of CMT in and around Patna along with the evaluation of CMT histotypes by FNAC, histological grading and immunohistochemical studyof HER-2, PCNA and Cytokeratin (CK) as a diagnostic, proliferative and prognostic markers. Mammary gland tumours were most common in bitches aged 4-8 years, constituting 46.66% of cases. Labrador breed dogs showed the highest occurrence of CMTs, and obese animals were more susceptible to mammary tumours. Histopathological analysis revealed that 80% of CMT cases were malignant, with the remaining 20% being benign. Among 24 malignant cases, grading showed five cases in grade I, eleven in grade II, and eight in grade III. Immunohistochemical analysis showed HER-2 overexpression in 8% of cases, moderate membrane expression in 20.83% of CMT cases. Moderate positive nuclear PCNA staining were found in in 62% cases. Cytokeratin exhibited moderate cytoplasmic immunoreactivity in 30% of cases, while strong immunoreactivity was observed in 42% of cases.Our study concludes that a combined assessment using a panel of markers including CMT markers, proliferative markers (PCNA), and prognostic markers (CK) can significantly aid in predicting the behaviour of mammary tumours.